Criminal Application by Judges Against Defendants of Mining Without Permits in Forest Areas - Lidya Ari Vega Jacob; Ariawan Gunadi (Jurnal Syntax Transformation, 2023)
The use of criminal law in dealing with criminal acts of mining without a permit certainly does not always involve criminal sanctions, but sanctions can also be applied which have the same status as criminal sanctions. This research was conducted to determine the validity of the law related to criminal acts of mining without a permit in forest areas, to determine the criminal liability of defendants in criminal acts of mining without permits in forest areas according to Indonesian law and to find out the application of criminal penalties by judges to defendants of criminal acts of mining without permits. in forest areas (Study Decision No. 53/Pid.Sus/2021/PN Wgw). This research method uses normative juridical research with a statutory approach and a case approach (the cash approach). The research results show that the legal validity related to criminal acts of mining without a permit in forest areas has been stated in Law Number 4 of 2009 concerning Mineral and Coal Mining (UU Minerba) and other applicable legislation where perpetrators who commit violations without permits will be given administrative sanctions. in the form of compensation according to the level of damage caused to the state. As well as criminal liability for defendants of criminal acts of mining without a permit in forest areas according to Indonesian law, they will be subject to criminal action in accordance with applicable legislation, such as being subject to sanctions in the form of administrative sanctions. And the application of punishment by the judge to the defendant for the crime of mining without a permit in a forest area (Study Decision No. 53/Pid.Sus/2021/PN Wgw) has been carried out as stated in Law no. 32 of 2009 concerning Environmental Protection and Management by applying other appropriate legal bases from the laws and regulations that regulate the criminal act of mining without a permit in forest areas.